Women who offend - McIvor, Gill, 1959- (Research highlights in social work, 2004)
Presenting research that will underpin effective practice with women who offend, this unique and thought-provoking text aims to help professionals meet the needs of this group as well as providing a theoretical resource for policy makers and academics. The authors, coming from a variety of professional and research perspectives, discuss important issues concerning women in the criminal justice system, including: the increase in custodial sentences for women; black women in prison; patterns of female offending; drug use and the criminal justice system; the needs of women on release from prison.